Cardiac sarcoidosis defined by cardiovascular magnetic resonance: patient characteristics and outcomes - Emhemed, Mohamed (Department of Medicine, 2023)
Introduction: Sarcoidosis is an inflammatory disorder that affects multiple systems. On histologic examination, sarcoidosis is defined by the production of non-caseating granulomas. Cardiac sarcoidosis (CS) is common, occurring in 20% or more of patients with systemic sarcoidosis, but because many people with CS may have nonspecific clinical manifestations or subclinical disease, the real extent of the disease prevalence is uncertain and possibly underestimated. Methods: Medical records of patients with CS diagnosed by cardiovascular magnetic resonance (CMR) were selected for inclusion into this study. We identified patients with a diagnosis of CS by CMR between March 2005 and January 2018 at Groote Schuur Hospital, Cape Town, South Africa and included into the South African Cardiovascular Magnetic Resonance (SA-CMR) registry. The demographics, clinical profile, and outcomes of patients diagnosed with CS via CMR were summarised utilising proportions, medians with interquartile ranges (IQRs), and means with standard deviations (SDs), as appropriate. Fisher's exact test was utilised to compare proportions, while T tests and Mann-Whitney U-tests were utilised to compare means and medians, respectively. Statistical Package for Social Sciences (version 26) program was used to analyse the data. Results: Medical records of 35 patients with a confirmed diagnosis of CS using CMR during the study period were identified. There were 21 (60%) males, and a male: female ratio of 1.5:1. The mean age of study participants was 50.3 ± 11 years. Most patients (84%) were overweight and obese, and comorbidities included hypertension (9%) and diabetes mellitus (3%). Nearly a quarter (23%) of patients presented with complete heart block and a third (31%) had ventricular tachycardia (VT) as the initial presentation. Half (54%) of patients had a permanent pacemaker or implantable cardioverter defibrillator implanted. A third (34%) of patients had evidence of acute myocardial oedema on T2-weighted imaging and T2 mapping, and 91% of subjects had evidence of focal fibrosis/infiltration on late gadolinium enhancement (LGE). Most patients (80%) had normal pericardial thickness and small pericardial effusions (< 1 cm) were noted in 49%. Extra-cardiac findings of sarcoidosis were characterised by hilar lymphadenopathy and pulmonary interstitial involvement (49%) and pleural effusions (11%). There were no deaths during the study period and median follow-up of 7 years. Conclusions: Sarcoidosis is a granulomatous systemic multiorgan condition that is a challenge to diagnose and manage in many settings. The availability of CMR has made it possible to diagnose CS noninvasively. We show that in our setting CS is characterised by oedema in a third of patients and evidence of LGE in almost all patients. Heart block and VT are common presentations; however, the prognosis is good with modern device therapies once the diagnosis has been made.